2017
DOI: 10.1093/biolre/iox114
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of individual rhesus macaque oocytes and preimplantation embryos†

Abstract: Early mammalian embryonic transcriptomes are dynamic throughout the process of preimplantation development. Cataloging of primate transcriptomics during early development has been accomplished in humans, but global characterization of transcripts is lacking in the rhesus macaque: a key model for human reproductive processes. We report here the systematic classification of individual macaque transcriptomes using RNA-Seq technology from the germinal vesicle stage oocyte through the blastocyst stage embryo. Major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Although the current studies were performed in the mouse, TRPM7, CACNA1H, and TRPV3 are all expressed in human oocytes and TRPM7 and TRPV3 are expressed in macaque oocytes as indicated by RNA sequencing (45)(46)(47)(48). Furthermore, there are numerous missense or loss of function (LoF) mutations identified in human TRPM7 (480 missense, 27 LoF), CACNA1H (1,045 missense, 10 LoF), and TRPV3 (312 missense, 23 LoF) (see Exome Aggregation Consortium browser at exac.broadinstitute.org; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Although the current studies were performed in the mouse, TRPM7, CACNA1H, and TRPV3 are all expressed in human oocytes and TRPM7 and TRPV3 are expressed in macaque oocytes as indicated by RNA sequencing (45)(46)(47)(48). Furthermore, there are numerous missense or loss of function (LoF) mutations identified in human TRPM7 (480 missense, 27 LoF), CACNA1H (1,045 missense, 10 LoF), and TRPV3 (312 missense, 23 LoF) (see Exome Aggregation Consortium browser at exac.broadinstitute.org; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Global transcriptomics techniques, such as RNA sequencing (RNA-seq), have recently allowed researchers to determine the whole transcriptome even from single cells (Hwang et al, 2018). RNAseq has already successfully been applied to macaque (Chitwood et al, 2017) and human oocytes (Zhao et al, 2019). However, no previous research has investigated the complete transcriptomic profile of oocytes from endometriosis patients compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…The development of single cell RNA sequencing has overcome some of these limitations, although it still requires linear amplification of cDNA prior to sequencing. It should be noted that this technique has been successfully used to identify changes in mRNA abundance in rhesus macaque, bovine, mouse, and human oocytes and/or embryos 15 19 . One-step RT-PCR assays have also been developed but a NCBI search showed that the majority of published data used this technique to primarily detect viral load in mammalian samples.…”
Section: Introductionmentioning
confidence: 99%